The role of children's right in society (Journal of actual problems of jurisprudence, 2021)
Today’s child is a generation, tomorrow is our future! In order for our future to be bright, the educationand upbringing of the current generation must be perfect and their rights must be protected. Aperson who can defend his rights, of course, protects the rights of his state.Special rights of children, their protection from threats, discrimination and vulnerability. These provisionsare enshrined in the International Convention for the protection of the rights of the child andauxiliary documents.Individuals who committed crimes in adolescence have a very high probability of committing crimesin adulthood. The factor that affects them is that they suffer from a lack of hope for their future and fromjoining a normal life and society.After studying , since the age of liability is 14 years, we often study juvenile delinquency. However,the basis for raising a child in the right direction and determining his attitude to society and his attitudeto his environment begins in infancy. taking into account all the factors that affect the child, we needchange our view of teenage criminality.In the Republic of Kazakhstan, all laws are classified in accordance with a single system, for example,we have a criminal code, a civil code, an administrative code or a labor code. With the adoptionof the above-mentioned codes in our country, we see only positive effects. Each law applies its own ruleand regulates relations in a certain system. This is exactly what we need to adopt the “code of children’srights” for teenagers and children of our homeland.Key words: Child, Law, teenager, crime, criminal liability.